Konstruksi Hukum Ekonomi Syariah Menurut M. Quraish Shihab - Bashori, Akmal (Sharia Faculty Islamic Economic Law Study Department, 2025)
This article provocatively examines the methodological construction of M. Quraish Shihab’s thought in reconstructing Islamic economic law in Indonesia through the framework of Imre Lakatos’s scientific research programme (SRP). Using qualitative research and content analysis, it explores Shihab’s thought, which situates maqāṣid al-sharī’ah, social justice, and rationality as its main epistemological pillars. In contrast to the legalistic approach that often constrains the discourse of fiqh, Shihab offers a paradigm of Islamic economic law that is adaptive, ethical, and contextual, making it more responsive to contemporary social, economic, and political transformations in Indonesia. From the perspective of SRP, Shihab’s thought can be read as a research programme with a normative hard core centered on maqāṣid and a methodological protective belt flexible enough to respond to global challenges. This article demonstrates that such a paradigm is not merely a reinterpretation of the law, but a serious effort to build a theoretical foundation that resists the stagnation of classical uṣūl al-fiqh. Thus, Shihab’s ideas open the way for Islamic economic law in Indonesia to emerge as more progressive, humanistic, and relevant amid the currents of modern globalization.